Constructing Mary through Pilgrimages: Lived Catholic Mariology in Poland - Niedźwiedź, Anna (Religions, 2023)
This article presents selected aspects of Marian pilgrimages in the context of lived Catholicism in Poland. Lived Catholic Mariology is a concept introduced in this paper and discussed in terms of the intimate as well as communal relationships people establish with Mary through and in various rituals (e.g., pilgrimages), sites (e.g., shrines) and objects (e.g., images). Links between materializing Mary through images; affective, sensual and corporeal religious experiences; and community bonding are presented. They are discussed by drawing on approaches that refer to material religion, religion as mediation, concepts of sensational forms, and aesthetic formations. When examining the centrality of Marian images in Polish pilgrimage practices, this paper focuses on earlier developments, especially (1) those connected with the growth of Marian shrines during the Counter Reformation period and (2) the role played by traditional and innovative Marian pilgrimages during the Communist period in Poland (1945–1989). The final part of the paper refers to the recent changes connected with political polarization of Polish society, the process of radicalization through right-wing discourses that embrace Marian imagery and pilgrimages, the decline of Roman Catholicism and Catholic practices among Poles, and emerging alternative currents relating to Mary and pilgrimages in religious and secular contexts. Referring to various historical and current examples, this paper proposes seeing pilgrimages through the lived religion approach with a focus on materiality and mediatory dimension of religion.